The case against free speech : the First Amendment, fascism, and the future of dissent - Moskowitz, P. E., 1988- (Bold Type Books, 2019)
"A hard-hitting expose that shines a light on the powerful conservative forces that have waged a multi-decade battle to hijack the meaning of free speech--and how we can reclaim it." -- From Amazon.com.